Consensus on measurement of core dataset for AE treatment research registries. (1st September 2019) - Vermeulen, F.M.; Gerbens, L.A.A.; Bosma, A.L.; Apfelbacher, C.J.; Irvine, A.D.; Arents, B.W.M.; Barbarot, S.; Deleuran, M.; Eichenfield, L.F.; Manca, A.; Schmitt, J.; Vestergaard, C.; et al.
Summary: Moderate‐to‐severe atopic eczema (AE) is often treated with phototherapy (light treatment) or systemic therapy (medication that works throughout the whole body). Long‐term data on effectiveness and safety of these treatments is currently missing. To address this issue, data on paediatric and adult patients who use or used these treatments in a real‐life setting should be collected in national research registries. Ideally, these national registries should be compatible, so that data can be combined and analysed from as many patients as possible (which is needed to find rare side‐effects, for example). Therefore, every country needs to collect the same data in the same way. For this purpose the international TREatment of ATopic eczema (TREAT) Registry Taskforce has been established. It has already standardised which items need to be measured (e.g. disease severity, side effects). This study addresses the two remaining issues: how and when to measure these items. To determine how to measure the items (i.e. which measurement instruments to use), the authors used the recommendations from the Harmonising Outcome Measures for Eczema (HOME) initiative, relevant literature (published scientific studies), an already existing AE registry in Germany, and expert opinions. The proposals were discussed at multiple meetings and via email. This resulted in agreement (consensus) on how to measure the already standardised item‐set. The issue of when to measure the items, the follow‐up frequency, was resolved with an online survey. Consensus was reached on a minimum follow‐up frequency of 4 weeks after starting treatment, then every 3 months whilst on treatment and every 6 months whilst off treatment. A complete core dataset is now available that will help with the standardised collection of data of paediatric and adult AE patients on photo‐ and systemic therapies. This will help, in time, answer questions on the long‐term effectiveness and safety of these treatments and improve care for moderate‐to‐severe AE patients.